(untitled) (World Science, 2021)
The nature of the formation of a hard crust in the mold is studied, taking into account the shrinkage of the workpiece during solidification. Comparison of the geometric shapes of the sleeves of the leading manufacturers from Germany, Italy, Japan. It is shown that defects in the billet crust originating in the mold cannot be corrected by subsequent cooling conditions. At the exit from the mold, the ingot crust must be of uniform thickness and withstand the ferrostatic pressure of liquid steel in order to prevent metal breakthroughs. This requires the organization of an intensive and continuous heat removal from the liquid steel to the cooling water in the crystallizer. The processes of heat removal from the surface of the solid crust of the workpiece through the walls of the mold liner are of decisive importance from the point of view of the dynamics of the growth of the solid phase and, as a consequence, the formation of surface and subsurface defects. To ensure high productivity and the required surface quality of the billet, leading companies strive to optimize the geometric shape of the mold sleeve, departing from classical designs.